Reframing households' food waste prevention behaviour: a conceptual unified framework proposition integrating religiosity/ Muhammad 'Arif Aizat Bashir ... [et al.] - Bashir, Muhammad 'Arif Aizat; Mohd Zahari, Mohd Salehuddin; Zulkifly, Muhammad Izzat; Abd Majid, Hairul Nizwan (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Out of many matters in the global environmental issues, household food waste is one of the concerns in today's world. Like many other countries, Malaysia is also facing the same issue, and it is expected to continuously aggravate in years to come. Even with the efforts and campaigns made by the Malaysian government and non-governmental organisations (NGOs), food waste is still escalating yearly. This issue comes into question whether Malaysian households possess adequate environmental systems knowledge or not, as several previous studies suggested that individuals who display higher levels of general environmental knowledge tend to demonstrate pro-environmental behaviour, which includes food waste prevention. Therefore, efforts to improve the quality of environmental situations, coupled with detrimental impacts of food waste that worsen from time to time, demand new ways of thinking about connections between households' environmental system knowledge and their attitudes towards food waste prevention behaviour. The proposed conceptual unified framework argues that understanding the environmental systems knowledge is essential in determining the success of food waste prevention behaviour through the proper environmental attitude, with the insertion of religiosity factor as a potential catalyser. In other words, this research note is an effort to understand the role of environmental system knowledge and the mediating effect of pro-environmental attitudes towards households' food waste prevention behaviour. The religiosity factor is integrated as a moderator.